Relationship between academic procrastination and academic achievement of postgraduate students - Mallika Gayary; Sima Kalita (Journal of Education and Health Promotion)
Background: The current research aims to explore the correlation between academic procrastination and students’ academic achievementand to examine the impact of academic procrastination on academic performance. This study addresses the challenges linked to delaying or avoiding academic tasks, which have the potential to negatively affect students’ success in their academic pursuits. Materials and Methods: The present research adopts a descriptive survey design and focuses on postgraduate students from Gauhati University (Session: 2022–2023). The study sample comprises 235 postgraduate students, consisting of 117 males and 118 females, and is further categorized into 115 Arts and 120 Science students. The selection of participants was done with the help of the stratified random sampling technique. The tool employed for the data collection was a self-designed scale specifically created for assessing the academic procrastination of postgraduate students. Statistical analyses were conducted to assess the null hypotheses associated with the various objectives of the study. The tests employed included Chisquare, Pearson coefficient of correlation, and regression analysis. Results: According to the current study, almost all the students procrastinate academically; the only difference is that some procrastinate more, while some procrastinate less, and gender and stream of education do not influence in the level of procrastination. It is also found through the current study that academic procrastination and academic achievement have a negative but significant relationship, which indicates that when there is an increase in academic procrastination, there is a low academic achievement and vice versa. Conclusion: Academic procrastination and academic achievement have a negative but significant relationship, and academic procrastination is significantly influenced by academic achievement of students. Therefore, measures should be taken to solve the problem of academic procrastination.